A utilização de dispositivos móveis como ferramenta de ensino-aprendizagem em sala de aula - Knittel, Tânia Filomena (2014)
In the field of Education today, we must take into consideration the fact that our students were born in the age of the internet and technologic boom. Video games and computers, faster and more advanced than ever, are part of their routine. According to Marc Prensky (2010), who specialized in technology and education at Yale University, children today are born in a world characterized by technology and digital media, and thus would have their cognitive profile altered. The present study, titled The Use of Mobile Devices as Teaching and Learning Tools in Classrooms, has the goal of identifying possible applications of the use of mobile devices as learning artifacts, as well as analyzing challenges, perspectives and possibilities for both learners and educators. The theoretical framework used as foundation for the argumentation is the Activity Theory, which emphasizes the importance of student action during the learning process (MATTAR, 2013), has as main contributors Vygotsky, Luria, Leontiev and Engeström and as main concept the unity of human consciousness and activity. The methodology used was the study of multiple cases with both a qualitative and quantitative approach, with descriptive and interpretative investigation based on an exploratory perspective that allowed a diversified set of data collection tools: interviews, questionnaires and investigation of the different issues in the focus group. The research analyzed mobile devices as mediation devices for the development of skills and abilities in order to face future challenges such as: critical thinking, problem solving, collaboration, communication, creativity, and innovation skills in classroom activities. The participating subjects were students and teachers in a private school located in the Southern Zone (Zona Sul) of the city of São Paulo. Final considerations of the study evidence mobile devices as a reality in students day-to-day lives, furthermore, in order for them to be used in the classroom, planning is required to allow for resignification by students and teachers, who play a fundamental role as mediators. Research findings show limiting factors, among them distraction and reduced screen size. However, the wide variety of functionalities present in such devices, such as applications, games, books and films, in addition to facilitating real time data and information access, make the use of smartphones and tablets for educational purposes ever more appealing